Avaliação do estado nutricional, ingestão proteica e qualidade de vida de indivúduos cirróticos com encefalopatia hepática - Augusti, Lais [UNESP] (2015)
Hepatic encephalopathy (HE) has high prevalence among cirrhosis complications and has a big impact on quality of life of patients. Additionally, the nutritional status of these patients is important and independently linked to morbidity and mortality. For this reason, nutritional evaluation is essential to provide early nutrition diagnosis, allowing the start of the dietary treatment. However, the assessment of nutritional status of these patients is a challenge because many of the tools applied to the healthy population can be altered by water retention and muscle depletion, quite common in cirrhotic. These patients should receive high-calorie and high-protein diet, but the protein intake is historically a controversial point in the dietary treatment of cirrhotic individuals. The aims of this study were to evaluate the nutritional status of cirrhotic subjects with HE by different methods, investigate their food and protein intake and their quality of life, observing the relations of these factors to each other. This was a cross-sectional study that included 60 patients, whose dietary intake was assessed through 24-hour recall, quality of life evaluated using the SF-36 questionnaire and the nutritional status by bioelectrical impedance analysis (BIA), dual energy X-ray absorptiometry (DEXA), anthropometric assessment and handgrip strength (HGS). The mean age was 56.1 ± 12.9 years, and 61.7% of subjects had overt HE (the remaining patients had the subclinical form). The body mass index (BMI) detected a high prevalence of overweight and obesity (56,7%), whilst BIA and DEXA pointed a high percentage of body fat (29.8 ± 8.0 ± 7.0% and 30.1%, respectively). Other measures such as handgrip strength and thickness of the adductor pollicis muscle (APM) showed higher rates of undernourished subjects: 81.7% and 73.3%. Through the appendicular muscle mass index (AMMI), 16.7% of the sample was classified as sarcopenic and 7.4% with sarcopenic ...